KELAYAKAN FINANSIAL AGROINDUSTRI PEKTIN DAN PAKAN TERNAK TERFERMENTASI BERBAHAN BAKU KULIT PISANG - Shanti Akhiriani; Soetriono Soetriono; Nurhayati Nurhayati (JURNAL AGROTEKNOLOGI, 2014)
Banana peel has the potential to be processed into pectin and fermented feed products. This study aims to determine the financial feasibility of the agro-industry of banana peel pectin and fermented feed, and sensitivity to the increasing of the raw material prices, rising prices and declining selling prices. The study used a descriptive and analytical approach. The results showed that pectin agro-industry and fermented feed from banana peel as raw material feasible to be developed based on five criteria: Net Present Value (NPV), Gross B / C, Net B / C, Internal Rate of Return (IRR) and Payback Period (PP). Banana peel pectin agroindustry was feasible to manage based on five financial feasibility criteria, including: (1) Net Present Value (NPV) of IDR 720,114,699.00 (> 0); (2) Gross B/C of 1.06 (> 1); (3) Net B/C of 2.34 (> 1); (4) Internal Rate of Return (IRR) of 40.89% (> 13%); and (5) Payback Period (PP) of 2.9 (<10 years). Fermented animal feed agroindustry was feasible to manage based on five financial feasibility criteria, that is: (1) NPV of IDR 366,118,110.00 (> 0); (2) Gross B/C of 1.16 (> 1); (3) Net B/C of 1.93 (> 1); (4) IRR of 32.54% (> 13%); and (5) PP of 3.7 (<10 years).Keywords: financial feasibility, banana peel, pectin, fermented feed, sensitivity